A new construction of quantitative screening designs. Issue 1 (2nd January 2019) - Chatterjee, K.; Georgiou, S. D.; Koukouvinos, C.; Stylianou, S.
ABSTRACT: This paper provides a new methodology to construct quantitative screening designs. Some examples of 3-level designs are presented to illustrate the method. The theoretical properties of the derived designs are also explored. An advantage of the presented designs is that they exist in cases where the classical screening designs cannot exist. The above method leads to the construction of many new large orthogonal designs with nice properties. Turyn-type sequences of lengths n, n, n, n −1 and orthogonal designs are used to achieve the desirable structure. This approach also leads to the construction of new quadruples of directed sequences of lengths 2 n −1, 2 n −1, n, n and type( 3 n − 1, 3 n − 1 ) with zero non-periodic autocorrelation function (zero NPAF).